LECT2 Protects Nile Tilapia (Oreochromis niloticus) Against Streptococcus agalatiae Infection - Li, Qi; Zhang, Zhiqiang; Fan, Weiqi; Huang, Yongxiong; Niu, Jinzhong; Luo, Guoling; Liu, Xinchao; Huang, Yu; Jian, Jichang (Frontiers in Immunology, 2021)
Leukocyte cell-derived chemotaxin 2 (LECT2) is a multifunctional cytokine that especially plays an important role in innate immune. However, the roles of LECT2 in the immune response of the economically important fish Nile tilapia (Oreochromis niloticus) against bacterial infection remains unclear. In this study, a lect2 gene from Nile tilapia (On-lect2) was identified, and its roles in the fish’s immune response against bacterial infection were determined and characterised. On-lect2 contains an open reading frame of 456 bp that encodes a peptide of 151 amino acids, as well as the conservative peptidase M23 domain. On-LECT2 is 62%–84% identical to other fish species and about 50% identical to mammals. The highest transcriptional level of On-lect2 was detected in the liver, whereas the lowest levels were detected in the other tissues. Moreover, the On-LECT2 protein is located mainly in the brain and head kidney. The transcriptional levels of On-lect2 substantially increased in the head kidney, brain, liver and spleen after Streptococcus agalactiae infection. Knockdown On-lect2 led to higher mortality due to liver necrosis or haemorrhage and splenomegaly. In vitro analysis indicated that the recombinant protein of On-LECT2 improved phagocytic activity of head kidney-derived macrophages. In vivo challenge experiments revealed several functions of On-LECT2 in the immune response of Nile tilapia against bacterial infection, including promotion of inflammation, reduction of tissue damages and improvement of survival rate.